2019
DOI: 10.1002/kjm2.12013
|View full text |Cite
|
Sign up to set email alerts
|

Disordered p53‐MALAT1 pathway is associated with recurrent miscarriage

Abstract: Recurrent miscarriage (RM) affects about 1% of couples; however, the etiologies of half of the cases remain unknown. P53, a negative cell cycle regulator, has been found to modulate the expression of several long noncoding RNAs (lncRNAs) and overexpressed p53 has been observed in RM patients. To investigate the relationship between p53 and lncRNAs in the pathogenesis of RM, we detected the expression of p53 and six candidate lncRNAs in the villous from 27 RM patients and paired healthy controls. We found the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Increasing evidence has shown that lncRNAs are involved in important biological processes, and the abnormal expression of lncRNAs has been implicated in the pathogenesis of RSA (Zhu et al, 2019). Research has shown that the level of MALAT1 is significantly reduced in villi from RM patients (Y. Wang et al, 2019). In this study, we also observed an obviously reduced expression of MALAT1 in the villous specimens from the RSA patients, which was consistent with that report.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that lncRNAs are involved in important biological processes, and the abnormal expression of lncRNAs has been implicated in the pathogenesis of RSA (Zhu et al, 2019). Research has shown that the level of MALAT1 is significantly reduced in villi from RM patients (Y. Wang et al, 2019). In this study, we also observed an obviously reduced expression of MALAT1 in the villous specimens from the RSA patients, which was consistent with that report.…”
Section: Discussionmentioning
confidence: 99%
“…studied the transcriptional regulation of lncRNA PVT1 and its effects on the biological behavior of trophoblasts, which might be related to the pathogenesis of RSA. A study (Wang et al, 2019)found that the levels of NEAT1 and metastasis associated lung adenocarcinoma transcript 1 (MALAT1) in tissue samples of patients with RSA were significantly decreased, and knockdown of the MALAT1 gene could lead to a decrease in proliferation and an increase in apoptosis of trophoblasts and primary chorionic trophoblasts.…”
Section: Lncrnas and Rsamentioning
confidence: 99%
“…Indeed, it has been shown that trophoblast dysfunction, due to compromised trophoblast infiltration and apoptosis, as well as multiple aberrant signal transduction pathways (64), could lead to adverse pregnancy outcomes, including uRPL (65). In detail, all the impaired pathways previously investigated in RPL trophoblast cells functions (including kisspeptin/GPR54 and PIBF/PR pathways, C4d and Bb, MBL, NOD1 and NOD2 via MAPK/p38 pathway, miR-27a-3p/USP25 axis, Fas and FasL, PKC protein, CCNA2, TWIST, Prototype and Chimera-Type Galectins, miR-520 and PARP1, BMAL1 via SP1-DNMT1/DAB2IP pathway, EIF5A1 via ARAF-mediated activation of integrin/ERK signaling pathway, Stathmin-1, peroxiredoxin2are) are linked to trophoblast migration, proliferation, invasion and apoptosis processes potentially relevant for RPL pathogenesis (64,(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78). Less is known about potential immunological impaired processes induced by trophoblast dysfunction.…”
Section: The Fetal-maternal Interfacementioning
confidence: 99%